Examination of challenges and opportunities for resettled sugarcane farmers under the fast track land reform programme: case of Mkwasine Estate. - Munjanja, Murombo (Midlands State University, 2017)
Land reform programme remains a subject of controversy in various sects of the society. The invasion of sugarcane estates in Chiredzi district being one of the controversial ones with many some citizens believing it was a threat to national economy as new farmers are exposed to various challenges which affect production as compared to former white farmers. The other side of the society believing that fast track land reform brought opportunities for the new farmers to enhance economic growth. This is the background to this research in which challenges and opportunities for fast track resettled sugarcane farmers are examined as well as the solutions to the challenges faced. The objectives of the study were to find out the challenges, opportunities for resettled sugarcane farmers and solutions to the challenges faced by the farmers. The literature review in the research was provided on the definition of land reform, why land reform was done in Zimbabwe and also on the objective of the research. That is literature on the challenges faced by resettled farmers, literature on the opportunities for resettled farmers and solutions to the challenges faced by farmers. The research utilised both qualitative and quantitative methods in data gathering and analysis. The study population was 238 farmers and 12 managers from Mkwasine and a sample of 20 farmers and 5 managers was selected using the simple random sampling technique. Questionnaires and interviews were used to collect data and were complimented by field observations. Data was presented in both qualitative and quantitative methods. Questionnaires were distributed to sugarcane farmers and interviews were done with Mkwasine Estate company managers. Research findings reflected that farmers are facing challenges like lack of equipment and resources, health and education challenges and lack of support from both government and private organisations. Opportunities identified by the research include investment and industrialisation opportunities as well as employment and land ownership opportunities. The research also made recommendations which include increased government support, sugarcane farmers representation and reengagement with international organisations to enhance productivity among other recommendations.